Street Children Behavior in Criminology Perspective (Study of Salatiga City) - Hertanto, Husein Bima; Radhiyastama, Cahya; Pamungkas, Lindu Aji; Prasetyo, Heru; Ibriza, Bintar (Law Research Review Quarterly, 2019)
Salatiga City is one of the cities in Indonesia which is located in Central Java province which is not separated from the problem of street children. The number of street children to date does not mean the request did not make any effort to handle it. The research has been headed to analyse the behavior of street children in Salatiga City. Researchers use qualitative approaches. Data collection techniques through in-depth interviews, observations, and document studies. Data analysis includes domain analysis, taxonomist analyzers, and other components and istemakultural analysis. The results of the study showed a variety of social behavior of children's roads in the city of Salatiga, namely sopa manners, solidarity, socializing, and interaction of the opposite gender. Street children's behavior does not always diverge like the views of the general public, they still hold the value and norms in society such as manners and solidarity for street children.